Psychopathological Comorbidities and Clinical Variables in Patients With Medication Overuse Headache - Migliore, Simone; Paolucci, Matteo; Quintiliani, Livia; Altamura, Claudia; Maffi, Sabrina; D’Aurizio, Giulia; Curcio, Giuseppe; Vernieri, Fabrizio (Frontiers in Human Neuroscience, 2020)
Psychopathological profile of patients with Medication Overuse Headache (MOH) appears to be particularly complex. To better define it, we evaluated their performance on a targeted psychological profile assessment. We designed a case-control study comparing MOH patients and matched Healthy Controls (HC). Headache frequency, drugs consumption, HIT-6 and MIDAS scores were recorded. All participants filled in the following questionnaires: Beck Depression Inventory II Edition (BDI-2), trait subtest of State-Trait Anxiety Inventory (STAI-Y), Difficulties in Emotion Regulation Scale (DERS), Barratt Impulsiveness Scale (BIS-11), Toronto Alexithymia Scale (TAS-20). The primary endpoint was to establish if MOH patients have an altered psychopathological profile. The secondary endpoint was to establish whether a worst profile correlates with worsening of headache and disability measures. We enrolled 48 consecutive MOH patients and 48 HC. MOH patients showed greater difficulty of recognition/regulation emotions (DERS, TAS-20), depression (BDI-2), anxiety (STAI-Y) and impulsiveness (BIS-11). We found a positive correlation among DERS, BDI-2, STAI-Y and BIS scores and MIDAS and HIT-6 scores and among DERS and headache frequency and drugs consumption. MOH patients showed a high rate of emotion regulation difficulties, depression and anxiety, which may negatively affect their headaches. The ability to regulate/recognize emotions may play a central role in sustaining medication overuse.